2009
DOI: 10.1149/1.3005562
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Morphological and Optical Properties of Sputtered Indium Tin Oxide Thin Films by Adopting Ultralow-Pressure Sputtering

Abstract: The morphological and optical properties of indium tin oxide ͑ITO͒ thin films deposited by an ultralow-pressure dc magnetron sputtering ͑ULPS͒ method followed by postannealing treatment at 250°C are reported. The surface roughness of the film ͑R rms : 0.5 nm͒ deposited using ULPS was about 5 times lower than that of the film ͑R rms : 2.7 nm͒ sputtered using a pressure of 6.7 ϫ 10 −1 Pa. ITO thin films with a low resistivity of 3.7 ϫ 10 −4 ⍀ cm were also achieved using a continuous two-step deposition process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…We speculated that the dense structure of the ULPSZnO film with very narrow columns may have originated from the increasing kinetic energy of the sputtered particles and the restriction of growth of the columnar structure. 18 Figure 4 shows the measured XRR data for the ZnO films deposited by CSP and ULPS. The critical angle for the total external reflection for the ULPS-deposited ZnO film was larger than that for the CSP, indicating that the ULPS-ZnO film ͑5.21 g / cm 3 ͒ was denser than the CSP one ͑4.70 g / cm 3 ͒.…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the dense structure of the ULPSZnO film with very narrow columns may have originated from the increasing kinetic energy of the sputtered particles and the restriction of growth of the columnar structure. 18 Figure 4 shows the measured XRR data for the ZnO films deposited by CSP and ULPS. The critical angle for the total external reflection for the ULPS-deposited ZnO film was larger than that for the CSP, indicating that the ULPS-ZnO film ͑5.21 g / cm 3 ͒ was denser than the CSP one ͑4.70 g / cm 3 ͒.…”
Section: Resultsmentioning
confidence: 99%
“…The higher density of the ULPS-deposited SnO x films compared to CSP was attributed to the enhanced kinetic energy of the sputtered particles. 11,20 The energy loss of a sputtered particle as it passes through the sputtering gas can be estimated from the following equation of Meyer et al 21…”
Section: H426mentioning
confidence: 99%
“…[8][9][10] Recently, Huh et al reported the strong dependence of the electrical properties of indium-doped tin oxide ͑ITO͒ films on the sputtering pressure and thus the kinetic energy of the sputtered particles. 11 This study reports the fabrication of TFTs with a SnO x film as the channel layer by using ultralow pressure sputtering ͑ULPS͒, with a sputtering pressure lower than 1.3 ϫ 10 −1 Pa, compared to higher than 6.7 ϫ 10 −1 Pa for a conventional sputtering pressure ͑CSP͒. As the sputtering pressure was decreased from 6.7 ϫ 10 −1 to 6.7 ϫ 10 −2 Pa, the N d of the SnO x thin film was dramatically reduced 100-fold from 10 19 to 10 17 cm −3 , resulting in a transistor performance with a reasonable mobility and on-and off-current ratio ͑I on/off ͒.…”
mentioning
confidence: 99%
“…[1][2][3] Currently, tin-doped indium oxide (ITO) is normally adopted as typical material of TCEs due to its high optical transparency and low electrical resistivity. 4 However, demand for improving the performance of photonic devices requires the development of electrodes (or filters) with better electrical and mechanical (or flexible) properties. Because of its low optical loss and high conductivity, thin Ag films have been commonly incorporated to form oxide/metal/oxide (OMO) multilayers, which exhibit low resistivity and high visible transmittance.…”
mentioning
confidence: 99%